Effect of intramolecular disulfide bond of bovine lactoferricin on its molecular structure and antibacterial activity against Trueperella pyogenes separated from cow milk with mastitis - Jie Pei; Lin Xiong; Min Chu; Xian Guo; Ping Yan (BMC Veterinary Research, 2020)
Abstract Background Lactoferricin (Lfcin) is an antimicrobial activity center of lactoferrin, produced by hydrolysis from the N-terminal of lactoferrin. It was hypothesized that the intramolecular disulfide bond in Lfcin could affect its antibacterial function through influencing its molecular structure. To prove this hypothesis, bovine Lfcin (bLfcin) and its two derivatives, bLfcin with an intramolecular disulfate bond (bLfcin DB) and bLfcin with a mutation C36G (bLfcin C36G), were synthesized, purified, and identified. The circular dichroism spectra of the peptides were detected in solutions with different ionic and hydrophobic strength. The antibacterial activity of the peptides against Trueperella pyogenes, separated from cow milk with mastitis, were determined. Results The secondary structure of bLfcin DB showed more β-turn and less random coil than the other peptides in H2O, similar ratios of secondary structures with bLfcin and bLfcin C36G under ionic conditions, and close percentages of secondary structure with bLfcin under hydrophobic conditions. The synthetic peptides exhibited strong antimicrobial activity against T. pyogenes isolates, T. pyogenes ATCC 19,411, and E. coli ATCC 25,922. The antimicrobial activities of the three peptides were greater against T. pyogenes than against E. coli, and bLfcin DB exhibited higher antibacterial activity compared with its derivatives. Conclusions The intramolecular disulfide bond could change the molecular structure of bLfcin under alternative ionic strengths and hydrophobic effects, and the formation of the disulfide bond is beneficial to executing the antibacterial function of bLfcin.